Composite dielectric film, metallized film and capacitor
By adopting the sandwich structure of composite dielectric films in film capacitors and using the modified nanoparticle dispersion layer, the problem of low dielectric constant at high temperatures is solved, and higher dielectric performance and high temperature resistance are achieved.
Patent Information
- Application Number
- CN202411372167.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polymer film capacitors exhibit low dielectric constant and poor high temperature resistance in high temperature environments, which are difficult to meet the high requirements of new energy-related equipment for fast charging and discharging.
The sandwich structure design of composite dielectric film is adopted, including a base layer, a deposited layer and a cover layer. The deposited layer is a modified nanoparticle dispersion layer, and the dielectric performance is improved by surface hydroxylated nanoparticles modified by silane coupling agent.
It effectively improves the dielectric properties of composite dielectric films, including increased dielectric constant and reduced dielectric loss, and is suitable for new energy equipment in high temperature environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thin film materials, and in particular relates to a composite dielectric film, a metallized film and a capacitor. Background Art
[0002] With the development of new energy related industries, the requirements for power-related equipment are getting higher and higher. In wind power, hybrid vehicles, and even military-related electromagnetic pulse equipment, the requirements for fast charging and discharging equipment are getting higher and higher. Among them, the performance requirements for film capacitors are getting higher and higher. Traditional polymer film capacitors have poor high temperature resistance and low dielectric constant, which can hardly meet higher usage requirements. Summary of the invention
[0003] In view of the problems of the prior art, the present application proposes a composite dielectric film, a metallized film and a capacitor.
[0004] The specific technical solutions are as follows:
[0005] The first aspect of the present application provides a composite dielectric film, comprising a base layer, a deposition layer and a covering layer, wherein the base layer and the covering layer are organic polymer layers, the deposition layer is a modified nanoparticle dispersion layer, and the modified nanoparticles are surface hydroxylated nanoparticles modified by a silane coupling agent.
[0006] Furthermore, the organic polymer layer includes polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide, and feasible grafted modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide, as well as feasible chemically modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide, and copolymers based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide.
[0007] Furthermore, the silane coupling agent is a silane coupling agent containing an epoxy group.
[0008] Furthermore, the deposition layer is formed by surface deposition.
[0009] Furthermore, the thickness of the deposited layer is 100 nm±10 nm, the uniformity RMS is <5 nm, and the coverage density is 50%.
[0010] The second aspect of the present application provides a metallized film, which comprises the composite dielectric film and a metal layer formed on a cover layer or a base layer by evaporation.
[0011] A third aspect of the present application provides a capacitor, wherein the cell of the capacitor is made of the metallized film.
[0012] The beneficial effects of the present invention are as follows: the composite dielectric film of the present invention uses a sandwich structure to design the interface structure of the surface hydroxylated nanoparticles modified by the silane coupling agent, which can effectively improve the dielectric properties of the composite dielectric film. DETAILED DESCRIPTION
[0013] The present application provides a composite dielectric film, which includes a base layer, a deposition layer and a covering layer, wherein the base layer is an organic polymer material layer, the deposition layer is a modified nanoparticle dispersion layer, and the covering layer is an organic polymer material layer. The base layer, the deposition layer and the covering layer are formed in sequence according to the order of the molding process. Therefore, when the covering layer is formed, it will fill in the nanoparticle dispersion gap and be connected with the base layer through the gap, thereby forming a tight multi-layer composite dielectric film.
[0014] Organic polymer materials include polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide, and feasible graft-modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide, as well as feasible chemically modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide, and copolymers based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, and polyetherimide.
[0015] The grafting modification is to introduce new side chains or functional groups into the main chain of the polymer by chemical reaction; the chemical modification is to chemically modify the polymer to introduce specific functional groups or change its chemical structure; the copolymer is a polymer having two or more monomer units prepared by copolymerization.
[0016] The base layer can be obtained by extrusion blow molding, extrusion casting, biaxial stretching, film casting, and casting.
[0017] The extrusion casting is a process of forming a film by extruding a polymer fluid and cooling and solidifying it through a cooling roller.
[0018] The biaxial stretching is a process for improving the mechanical strength and thermal stability of a film by stretching it during the film manufacturing process.
[0019] The cast film is a process of forming a film by coating a polymer melt or solution on a smooth cooled surface, followed by cooling and peeling.
[0020] The casting is a process of casting a polymer fluid onto a cooling belt and then solidifying it by cooling to form a film.
[0021] The deposition layer is formed by depositing the modified nanoparticles on the base layer by a surface deposition method, and the thickness is in the range of tens of nanometers to hundreds of nanometers.
[0022] The covering layer is an organic polymer layer formed by casting.
[0023] The modified nanoparticles deposited in the deposition layer are surface hydroxylated nanoparticles modified by a coupling agent, wherein the nanoparticles include nano silicon dioxide, nano barium titanate, nano calcium titanate, and nano ceramic particles.
[0024] The method for hydroxylating the surface of the nanoparticles is as follows: the clean and dry nanoparticles are placed in a prepared oxidant solution, ultrasonically treated for 2 hours, then washed with deionized water, and the washed nanoparticles are dried.
[0025] The oxidant solutions that can be used include aqueous hydrogen peroxide solutions and aqueous potassium peroxide solutions, and the concentration of the solutions is controlled at 3-8% (wt).
[0026] The method for preparing surface hydroxylated nanoparticles modified by coupling agents is as follows: adding a silane coupling agent to the surface hydroxylated nanoparticles, dispersing the nanoparticles in an organic solvent, and heating the nanoparticles while performing ultrasonic dispersion, and then centrifuging, washing, and drying the nanoparticles to obtain surface hydroxylated nanoparticles modified by coupling agents.
[0027] The silane coupling agent includes an epoxy group-containing silane coupling agent, an amino group-containing silane coupling agent, an acryloxy group-containing silane coupling agent, and a urea group-containing silane coupling agent.
[0028] Organic solvents include alcohol solvents, ketone solvents, ester solvents, ether solvents, aromatic hydrocarbon solvents, and polar aprotic solvents.
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments.
[0030] Example 1
[0031] The base layer and covering layer of the composite dielectric film are polyetherimide and polyetherimide respectively, the deposited layer is surface hydroxylated nano-silica modified by a coupling agent, the thickness of the deposited layer is 100nm±10nm, the uniformity RMS<5nm, the coverage density of the surface hydroxylated nano-silica modified by the coupling agent on the base layer is 50% (coverage rate), and the thickness of the base layer and the covering layer are 3 microns respectively.
[0032] The coupling agent used for modifying the surface hydroxylated nano-silica is γ-methacryloxypropyltriethoxysilane.
[0033] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 4.1, and the dielectric loss (10kHz) was 0.0056.
[0034] Example 2
[0035] The base layer and covering layer of the composite dielectric film are polyimide and polyimide respectively, the deposited layer is surface hydroxylated nano-silica modified by a coupling agent, the thickness of the deposited layer is 100nm±10nm, the uniformity RMS<5nm, the coverage density of the surface hydroxylated nano-silica modified by the coupling agent on the base layer is 50% (coverage rate), and the thickness of the base layer and the covering layer are 3 microns respectively.
[0036] The coupling agent used for modifying the surface hydroxylated nano-silica is γ-methacryloxypropyltriethoxysilane.
[0037] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 4.3, and the dielectric loss (10kHz) was 0.0053.
[0038] Example 3
[0039] The base layer and covering layer of the composite dielectric film are polyetherimide and polyethylene terephthalate respectively, the deposited layer is surface hydroxylated nano-silica modified by a coupling agent, the thickness of the deposited layer is 100nm±10nm, the uniformity RMS<5nm, the coverage density of the surface hydroxylated nano-silica modified by the coupling agent on the base layer is 50% (coverage rate), and the thickness of the base layer and the covering layer are 3 microns respectively.
[0040] The coupling agent used for modifying the surface hydroxylated nano-silica is γ-methacryloxypropyltriethoxysilane.
[0041] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.8, and the dielectric loss (10kHz) was 0.0055.
[0042] Example 4
[0043] The base layer and covering layer of the composite dielectric film are polycarbonate and polypropylene respectively, the deposited layer is surface hydroxylated nano-silica modified by a coupling agent, the thickness of the deposited layer is 100nm±10nm, the uniformity RMS<5nm, the coverage density of the surface hydroxylated nano-silica modified by a coupling agent on the base layer is 50% (coverage rate), and the thickness of the base layer and the covering layer are 3 microns respectively.
[0044] The coupling agent used for modifying the surface hydroxylated nano-silica is γ-methacryloxypropyltriethoxysilane.
[0045] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a fixture. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.9, and the dielectric loss (10kHz) was 0.0058.
[0046] Comparative Example 1
[0047] The base layer and the covering layer of the composite dielectric film are polyetherimide and polyetherimide respectively, and do not contain a deposition layer. The thickness of the base layer and the covering layer are 3 microns respectively.
[0048] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.1, and the dielectric loss (10kHz) was 0.0069.
[0049] It can be seen that the composite dielectric film including the base layer, the deposition layer and the covering layer has better dielectric properties than the composite dielectric film having only the base layer and the covering layer.
[0050] Example 5
[0051] The structure of the composite dielectric film is the same as that of Example 1 and is prepared by the following method:
[0052] The base layer is formed by biaxial stretching, and then a deposition layer is formed on the base layer by a vapor deposition process, and finally a covering layer is formed by a casting process.
[0053] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 4.1, and the dielectric loss (10kHz) was 0.0055.
[0054] Comparative Example 2
[0055] The composite dielectric film comprises a base layer and a covering layer, wherein the base layer and the covering layer are polyetherimide and polyetherimide respectively. The base layer contains surface hydroxylated nano-silicon dioxide modified by a coupling agent, and the addition amount of the surface hydroxylated nano-silicon dioxide modified by a coupling agent is 5% of the mass of the base layer.
[0056] The base layer is prepared by the following method:
[0057] Put clean and dry nano-silicon dioxide into a potassium permanganate aqueous solution, the concentration of the potassium permanganate aqueous solution is 5%, and the amount of potassium permanganate aqueous solution is 10 ml / g nano-silicon dioxide, and wash with deionized water after ultrasonic treatment for 2 hours, and dry the washed nano-particles;
[0058] Adding γ-methacryloxypropyltriethoxysilane to surface hydroxylated nano-silica and dispersing them in N,N-dimethylformamide, wherein the amount of γ-methacryloxypropyltriethoxysilane added is 3% of the mass of the surface hydroxylated nano-silica, and the amount of organic solvent used is 25 ml / g of the surface hydroxylated nano-silica, ultrasonically dispersing for 2 hours, maintaining the temperature at 50° C., and then centrifuging, washing, and drying to obtain surface hydroxylated nano-silica modified by a coupling agent;
[0059] Dissolve polyetherimide in DMF solvent, ultrasonically disperse surface hydroxylated nano-silica modified by coupling agent in DMF solvent, and mix the two uniformly;
[0060] The mixed liquid was coated on a 10cm*10cm glass plate, and the prepared film was placed in a vacuum oven at 50℃*16h; 180℃*6h, and the finished film was obtained after completing the heat treatment.
[0061] Copper electrodes were deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a fixture. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.5, and the dielectric loss (10kHz) was 0.0058.
[0062] It can be seen that the composite dielectric layer including the base layer, the deposition layer and the covering layer has better dielectric properties than directly mixing the surface hydroxylated nano-silica modified by the coupling agent into the base layer.
[0063] Comparative Example 3
[0064] The coupling agent in Example 5 was replaced with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (urea-containing silane coupling agent).
[0065] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.7, and the dielectric loss (10kHz) was 0.0062.
[0066] Comparative Example 4
[0067] The coupling agent in Example 5 was replaced with γ-acryloxypropyltriethoxysilane (silane coupling agent containing acryloxy group).
[0068] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.6, and the dielectric loss (10kHz) was 0.006.
[0069] Comparative Example 5
[0070] The coupling agent in Example 5 was replaced with N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (amino group-containing silane coupling agent).
[0071] The composite dielectric film was cut into a size of 10cm*10cm. Copper electrodes were first deposited on both sides of the film using a high vacuum resistance evaporation coating machine. The film coated with copper electrodes was then placed in a precision impedance analyzer and the copper electrodes were clamped using a clamp. The dielectric properties in the range of 100Hz-120MHz were tested at room temperature: the dielectric constant (10kHz) was 3.8, and the dielectric loss (10kHz) was 0.0059.
[0072] It can be seen that the use of different coupling agents for surface hydroxylated nano-dioxide modification will also affect the dielectric properties of the final composite film, and the silane coupling agent containing epoxy groups has the best performance.
[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them.
Claims
1. A composite dielectric film, characterized in that: The invention comprises a base layer, a deposition layer and a covering layer, wherein the base layer and the covering layer are organic polymer layers, the deposition layer is a modified nanoparticle dispersion layer, and the modified nanoparticles are surface hydroxylated nanoparticles modified by a silane coupling agent.
2. A composite dielectric film according to claim 1, characterized in that: The organic polymer layer includes polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide, and feasible grafted modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide, and feasible chemically modified materials based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide, and copolymers based on polyester, polyimide, polyethylene terephthalate, polycarbonate, polyurethane, polypropylene, polyetherimide.
3. A composite dielectric film according to claim 1, characterized in that: The silane coupling agent is an epoxy group-containing silane coupling agent.
4. A composite dielectric film according to claim 1, characterized in that: The deposited layer is formed by surface deposition.
5. The composite dielectric film according to claim 1, characterized in that: The thickness of the deposited layer is 100 nm±10 nm, the uniformity RMS is less than 5 nm, and the coverage density is 50%.
6. A metallized film, characterized in that: The invention comprises the composite dielectric film as claimed in any one of claims 1 to 5, and a metal layer formed on a cover layer or a base layer by evaporation.
7. A capacitor, characterized in that The capacitor core is made of the metallized film according to claim 6.
Citation Information
Patent Citations
Method for preparing high dielectric polymer composite film
CN103963408A
Polyimide-based composite film with sandwich structure and high energy storage density and preparation method of polyimide-based composite film
CN114559721A
Polysulfone / modified filler composite dielectric film material and preparation method thereof
CN115124838A
High-temperature-resistant polymer dielectric thin film material and thin film capacitor
CN115197452A
Polyetherimide dielectric composite material as well as preparation method and application thereof
CN115260762A